Health-Promoting Properties and Potential Application in the Food Industry of Citrus medica L. and Citrus × clementina Hort. Ex Tan. Essential Oils and Their Main Constituents - Tundis, Rosa (2023)
Citrus is an important genus in the Rutaceae family, with high medicinal and economic value, and includes important crops such as lemons, orange, grapefruits, limes, etc. The Citrus species is rich sources of carbohydrates, vitamins, dietary fibre, and phytochemicals, mainly including limonoids, flavonoids, terpenes, and carotenoids. Citrus essential oils (EOs) consist of several biologically active compounds mainly belonging to the monoterpenes and sesquiterpenes classes. These compounds have demonstrated several health-promoting properties such as antimicrobial, antioxidant, anti-inflammatory, and anti-cancer properties. Citrus EOs are obtained mainly from peels, but also from leaves and flowers, and are widely used as flavouring ingredients in food, cosmetics, and pharmaceutical products. This review focused on the composition and biological properties of the EOs of Citrus medica L. and Citrus clementina Hort. Ex Tan and their main constituents, limonene, -terpinene, myrcene, linalool, and sabinene. The potential applications in the food industry have been also described. All the articles available in English or with an abstract in English were extracted from different databases such as PubMed, SciFinder, Google Scholar, Web of Science, Scopus, and Science Direct.